The Health of Women and Girls: How Can We Address Gender Equality and Gender Equity? - Payne, Sarah (Seminars in Reproductive Medicine, 2015)
This article focuses on the health of women and girls, and the role of addressing gender inequalities experienced by women and girls. The health of both males and females is influenced by sex, or biological factors, and gender, or socially constructed influences, including gender differences in the distribution and impact of social determinants of health, access to health promoting resources, health behaviors and gender discourse, and the ways in which health systems are organized and financed, and how they deliver care. Various strategies to address the health of women and girls have been developed at intergovernmental, regional, and national level, and by international nongovernmental organizations. These include vertical programs which aim to target specific health risks and deliver services to meet women and girl's needs, and more cross-cutting approaches which aim at “gender” policy making. Much of this work has developed following the adoption of gender mainstreaming principles across different policy arenas and scales of policy making, and this article reviews some of these strategies and the evidence for their success, before concluding with a consideration of future directions in global policy.
Keywords: gender equity; gender equality; women's health; girl's health; gender mainstreaming